Component Placement Accuracy in Unicompartmental Knee Arthroplasty is Improved with Robotic-Assisted Surgery: Will it Have an Effect on Outcomes?. Issue 2 (July 2018) - Rauck, Ryan C.; Blevins, Jason L.; Cross, Michael B.
Bell et al.'s "Improved Accuracy of Component Positioning with Robotic-Assisted Unicompartmental Knee Arthroplasty: Data from a Prospective, Randomized Controlled Study" compared the accuracy of a robotic-assisted unicompartmental knee arthroplasty (UKA) using the MAKO Robotic Interactive Orthopedic Arm (RIO) system to a conventional UKA using standardized instrumentation. This review examines the authors' findings and their relevance to clinical practice. Bell et al. conclude that the MAKO RIO system leads to more accurate implantation of both the tibial and femoral components in UKA in the sagittal, coronal, and axial planes. This well-designed, level I study suggests what many arthroplasty surgeons assume about robotic assistance, which admittedly is of unknown clinical significance at this time. Evaluating this article in the context of the current literature provides valuable insight into areas in need of future investigation. The effect of implant positioning on long-term clinical outcomes and implant survivorship remains unclear. Long-term follow-up studies are needed to determine the role of robotic-assisted arthroplasty in the future.